Operational Experiment and Related Legal Issues in Latvia: An Overview - Grinciuns, Mārcis (European Journal of Sustainable Development, 2023)
Operational Activities Law of the Republic of Latvia states operational activities that are performed in order to prevent or detect criminal offences and to safeguard the independence of the State, its constitutional order and territorial integrity. This research focuses on “Operational experiment” which is an operational activity defined in Section 15, paragraph three of the Operational Activities Law. It allows Latvian law enforcement authorities to create specific circumstances (situations) in order to determine criminal purposes of persons. Usually, this activity is used to investigate illicit narcotic drug trafficking, corruption cases and other crime investigations where “test-purchase” operations are required. This article examines the part of the legal regulation for operational experiments that determines what situations are intended to be created when the measure is being implemented. Linguistic analysis and legal interpretation (translation) of the currently effective legal regulation for operational experiments in conjunction with the actual content of operational experiments that are put into practice showed that there are certain deficiencies in the legislation which occur in cases when it is necessary to create infringement situation which is not a crime. Such situations are created when it is necessary to determine if officials facing an infringement, which is not a crime, in the course of fulfilling their official duties, will act in accordance with duties assigned to their post or will ask the infringer (performer of the operational experiment) for a bribe. Keywords: operational activities, operational experiment, investigatory experiment, test purchase, undercover operations, entrapment, incitement, provocation, sustainable development.